Molecular markers enhance substantially the distinctness of alfalfa varieties for registration and protection - Paolo Annicchiarico; Nicolò Franguelli; Barbara Ferrari; Giacomo Campanella; Stefano Gualanduzzi; Margherita Crosta; Chiara Delogu; Giorgia Spataro; Nelson Nazzicari (The Plant Genome)
Abstract Plant varieties must satisfy distinctness, uniformity, and stability (DUS) requirements for registration. Morphophysiological trait‐based distinctness may be challenging for cultivars of major perennial forages. Our study focused on alfalfa (Medicago sativa L. subsp. sativa) with the aims of (a) comparing morphophysiological distinctness with molecular distinctness based on genotyping‐by‐sequencing (GBS) or the alfalfa DArTag panel, envisaging different statistical criteria for molecular distinctness, and (b) assessing the consistency of morphophysiological and molecular cultivar diversity. The 18 most grown Italian varieties were jointly reevaluated morphophysiologically and were characterized molecularly using three bulked DNA samples of 200 independent genotypes per cultivar. Morphophysiological distinctness was limited by correlations between traits and resulted in 39 non‐distinct cultivars in 153 paired comparisons and three cultivars distinct from any other. Best configurations for molecular distinctness featured about 10‐fold more polymorphic markers and 10‐fold lower average read depth per marker for GBS compared to DArTag. DArTag markers allowed for somewhat better variety distinction than GBS. They reduced to 11 the non‐distinct cultivars in paired comparisons and increased to 11 the completely distinct cultivars, based on a principal components analysis of allele frequencies followed by analyses of variance on cultivar principal component scores. This criterion achieved greater variety distinctness than cluster analysis with bootstrap values, discriminant analysis, or analysis of molecular variance. Morphophysiologically distinct cultivars were generally distinct molecularly, but not the reverse. Mantel's test revealed a modest consistency across morphophysiological and DArTag (r = 0.39) or GBS‐based (r = 0.46) measures of cultivar Euclidean distance. Our results and other considerations strongly encourage the adoption of molecular distinctness for alfalfa DUS.